2001
DOI: 10.1055/s-2001-15046
|View full text |Cite
|
Sign up to set email alerts
|

Häufigkeit der thrombophilen Faktor-V-Leiden- und Prothrombin-G20210A-Mutation bei Morbus Perthes - Eine Pilotstudie

Abstract: For the presented group of children with Perthes' disease, we did not find an increased rate of factor V or prothrombin mutations compared to the natural incidence. In accordance to other recent studies, our results do not support a link between inherited thrombophilic mutations and Perthes' disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…[23][24][25][26][27][28] While several studies suggest that Leiden's V factor is the potential causative factor for Legg-Calvé-Perthes disease 1,2,12-14 some studies do not show any correlation between this disease and thrombophilia. [16][17][18][19][20] The results reported by Hayek et al 21 do not imply thrombophilia in the pathogenesis of Perthes disease (4.83% in patients, 10% in controls). Similarly, the study by Franco et al 15 does not corroborate the association between Leiden's V factor and LCP (odds ratio: 1.36; 95% confidence interval: 0.32-5.84).…”
Section: Discussionsupporting
confidence: 50%
“…[23][24][25][26][27][28] While several studies suggest that Leiden's V factor is the potential causative factor for Legg-Calvé-Perthes disease 1,2,12-14 some studies do not show any correlation between this disease and thrombophilia. [16][17][18][19][20] The results reported by Hayek et al 21 do not imply thrombophilia in the pathogenesis of Perthes disease (4.83% in patients, 10% in controls). Similarly, the study by Franco et al 15 does not corroborate the association between Leiden's V factor and LCP (odds ratio: 1.36; 95% confidence interval: 0.32-5.84).…”
Section: Discussionsupporting
confidence: 50%
“…1,5,6,8,12 On the other hand, several authors found no relationship between Perthes' disease and thrombophilic disorders. [12][13][14][15][16]32,33 Hayek et al 13 studied 62 patients diagnosed with Perthes' disease and found no evidence to support a role of thrombophilia in the pathogenesis and evolution of the disease. Hresko et al 14 analyzed the value of screening for inherited thrombophilia in patients with Legg-Perthes disease and ruled it out.…”
Section: Discussionmentioning
confidence: 95%
“…[9][10][11] Several groups have investigated these hereditary factors of thrombophilia to establish whether they are involved in the development of Perthes' disease. 1,4,6,8,[12][13][14][15][16] We wanted to determine whether children with Perthes' disease have an increased incidence of congenital thrombophilia, so we evaluated the main hereditary factors that lead to venous thrombosis: factor V Leiden, G20210A prothrombin polymorphism, and C677T polymorphism of MTHFR.…”
mentioning
confidence: 99%
“…Vosmaer et al [8] report thrombotic component in the etiology of LCPD. Schmitz et al [9] study did not find an increased rate of factor V or prothrombin mutations in children with en with LCPD compared to the natural incidence. Kenet et al [10] found no genetic association between LCPD and increased genetic thrombophilia among patients compared with the control group.…”
mentioning
confidence: 81%